Evaluation of valuable chain in palm oil industry based on SCOR model: a case study. Issue 2 (2015) - Sutopo, Wahyudi; Maryanie, Dwi Indah; Yuniaristanto,
Indonesia is the largest producer and exporter of palm oil in the world, beating Malaysia which was used to be the largest producer in the world. However, Indonesia's derivative products still lag behind Malaysia because of low productivity. A good supply chain management is one of the causes why the development of Malaysia's more superior to Indonesia. This paper aims to evaluate the performance conditions of valuable chain in palm oil industry from upstream to downstream currently based on SCOR® model. Not only based on theory, but this paper also considers the real case condition by doing benchmark between companies in Indonesia and Malaysia. The result shows that from five performance attributes of SCOR, only reliability, responsiveness and assets attributes that have gaps with the performance value of benchmarking target while agility and cost attributes result the same value with benchmarking target. This means that palm oil mills in the Indonesia company that is benchmarked, needs to improve its supply chain related to those of third performance attributes.